2021
DOI: 10.1515/nanoph-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Surface-response functions obtained from equilibrium electron-density profiles

Abstract: Surface-response functions are one of the most promising routes for bridging the gap between fully quantum-mechanical calculations and phenomenological models in quantum nanoplasmonics. Among all currently available recipes for obtaining such response functions, the use of ab initio methods remains one of the most conspicuous trends, wherein the surface-response functions are retrieved via the metal’s non-equilibrium response to an external time-dependent perturbation. Here, we present a complementary approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…( 6)) will lead to a situation with a finite surface response. To appreciate this, we note that for a spatially varying local dielectric function 𝜀(x), the induced charge 𝜚(x) is given by [271] 1…”
Section: How To Determine Feibelman Parameters?mentioning
confidence: 99%
See 3 more Smart Citations
“…( 6)) will lead to a situation with a finite surface response. To appreciate this, we note that for a spatially varying local dielectric function 𝜀(x), the induced charge 𝜚(x) is given by [271] 1…”
Section: How To Determine Feibelman Parameters?mentioning
confidence: 99%
“…We emphasize that this concept of a spatially varying plasma frequency has found broad use, including Refs. [203,205,271,[276][277][278][279][280][281]. The idea of a smoothly varying profile has also been considerations of local-field corrections [282].…”
Section: Local-response Approximation With Equilibrium Electron-densi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent study has also shown that the quantum effect can be investigated using the local dielectric function in Eq. (4) [30].…”
Section: Equations For Localized Plasmons In Metal Nanostructures a Scalar Potential In The Quasi-static Approximationmentioning
confidence: 99%